PENGARUH KEKERASAN VERBAL ORANG TUA TERHADAP PERILAKU AGRESIF ANAK DI DESA LABUHAN TANGGA KECIL KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Rapina Rapina; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This research aims to know the influence of verbal violence of parents towards the child's aggressive behavior village Labuhan Tangga Kecil Subdistrict Bangko District Rokan Hilir. As for the population in this research is the parents who have children ages 5-6 years in the village of Labuhan Tangga Kecil Subdistrict Bangko District Rokan Hilir totalling 50 people samples. Method of this research is quantitative correlation to know the correation between independent variable and dependent variable. The technique of collecting data used quistioner in Likert scale form. The technique of analyzing data used scale test and statistic analitical by using SPSS program for Windows Ver.22. Based on the results of a test of the hypothesis there is significant positive influence between verbal violence of parents towards the child's aggressive behavior in the village of Labuhan Tangga Kecil Subdistrict Bangko District Rokan Hilir. It could be seen from the result of correlation cooficient that 0,840 and significant level is 0,000< 0,05. Relationship between the level of verbal violence with aggressive behavior included in this category is very strong with the value of the resulting determinant is the coefficient of KD = r ² x 100% = 70.5% had the meaning that the verbal violence gives the influence of 70.5% against the aggressive behavior.Key Words: verbal violence, aggressive behavior